(untitled) (Research, Society and Development, 2022)
Although it is now recognized how relevant it is that physical education classes are taught by a qualified teacher in their field, some public and even private schools in the Early Years of Elementary School still limit physical education activities to practices considered merely delegating this responsibility to the classroom teachers, who are professionals in the area of Pedagogy. This reality is no different at the Municipal School of Elementary and Primary Education “Councilman João Gonçalves de Sousa”, located in the municipality of Marizópolis, state of Paraíba. The choice of the theme was related to the objective of the research, which was to analyze the perceptions of teachers of the early years of the referred school about the physical education classes. It is a qualitative research, more precisely a case study. As for the data, they were collected from interviews. After this phase, the data were interpreted. The findings indicate that teacher educators know the importance of the physical education teacher in the early years’ classes, feel that they have a limited knowledge of the topics that need to be worked on in the classroom and admit that they give the classes a recreational character. They emphasized that the Physical Education teacher can assist in the integral development of the child by working on his / her skills and competences, making them more interactive and secure in front of their own world and the world as a whole.